EMPOWERING MADRASAH LIBRARY THROUGH INFORMATION LITERACY PROGRAM - Ruslan (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Humaniora Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The library's continued existence as a hub for information resources has been impacted by the current developments in information technology. This study looks at information literacy initiatives as a means of strengthening madrasah libraries in Indonesia using a literature-based approach. What kinds of crucial elements are included in the information literacy program offered by the madrasah and library? The findings of this study suggest that enhancing the role of madrasah libraries as hubs of knowledge and information can be achieved by providing them with information literacy programs. It is anticipated that this program will enhance students' aptitude for finding, evaluating, and critiquing information in addition to producing well-educated graduates who are prepared to compete in the global marketplace. The madrasah librarian must prepare a planned process and foster collaboration among madrasah stakeholders in order to strengthen the implementation of the information literacy program in the madrasah library.